Study of Environmental Impact in Tourism Development of Delta Areas, Buton Utara Regency, South East Sulawesi - Vita Kartikasari; Wa Ode Sitti Warsita Mahapati (International Conference on Coastal and Delta Areas, 2015)
International tourism market competition is forcing each country to diversify tourismproducts that uniqueness of each country. Tourism market has shifted from "product driven" go to"market driven". It means, consumers are increasingly concerned with efforts in environmentally sustainable tourism, quality of product and service consumer rights. Tourism development of coastal areas become an investment that gives the advantage of the social, physical, and biotic aspects. Therefore, research in the coastal area of Buton Utara Regency conducted at three locations with different ecosystem types, which include: Bonelipu Beach, Mangrove Ecotourism Kulisusu Bay, Labuan Marine Tourism. The data obtained through the primary and secondary data collection, interviews related to the physical and non-physical condition of the delta area, and survey to check the condition of the location.The environmental impact of tourism development in the coastal areas Bonelipu Beach, MangroveEcotourism Kulisusu Bay, Labuan Marine Tourism causes changes to tourist beaches, utilization rate changes sectoral, changes in the level of damage and change management.